Bureaucracy and Administration - Ali Farazmand (CRC Press Taylor & Francis Group, 2009)
Fifteen years have passed since the publication of the fi rst edition of the Handbook of Bureaucracy in 1994. Given that this period has been marked by an intense global movement of antibureaucracy, antigovernment, and antipublic service and administration, the following questions are quite natural: Why do we need another book on bureaucracy now? Does bureaucracy still matter? Th e answer to these challenging questions is that despite this intense negative attitude toward bureaucracy, global interest in the fi rst edition of this book has been overwhelming. Th e book has reached more libraries, university classrooms, and institutional leadership desks than was initially expected. What accounts for such an overwhelming success of the fi rst edition, and the continuing demand for an updated new edition, is itself a remarkable question that all of us in the fi eld of social sciences need to consider, understand, and appreciate. Th e world has become more complex, globalization of corporate capitalism and cultures as well as governance systems has become more rapid and widespread, and the tasks of public governance and administration have become more numerous and demand more institutionally tested solutions and ideas to meet the increasing challenges of the age of hyper-uncertainties. Strategic adaptation to global challenges of the age is an essential task for modern governance, but not all new and untested ideas can off er solutions to complex problems that require established institutional solutions. Bureaucracy is one of those ancient institutions that, despite many negative connotations attached to it, has persisted with durability, dependability, and stability—it has been tested for millennia.